Effekte von Fusionen in Kontinentaleuropa und Deutschland - Klaus Gugler; Dennis C. Mueller; B. Burcin Yurtoglu; Christine Zulehner (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
This paper takes a look at the effects of mergers in continental Europe over the past 15 years. We use a large panel of data on mergers to test several hypotheses. The effects of the mergers are examined by comparing the performance of the merging firms with control groups of non-merging and/or by controlling for changes in economic conditions by using common stock indices and the like. Comparisons are made on profitability, market values and sales. The results show that mergers on average do not result in significant increases in profits, but reduce sales of the merging firms and the value to their shareholders.
Keywords: 330; Fusion; Corporate Governance; Rentabilität; Marktwert; Absatz; Deutschland; Europa